Minocycline-Induced Scleral and Dermal Hyperpigmentation. Issue 3 (March 2017) - Haskes, Cheryl; Shea, Michael; Imondi, David
ABSTRACT: Purpose: To present a case of minocycline-induced blue scleral pigmentation and discuss the pathophysiology and differential diagnoses. The uses, mechanisms, and other adverse effects of minocycline will also be highlighted. Case Report: An elderly Caucasian male patient presented for routine ocular examination complaining of blue discoloration to the whites of his eyes. He was found to have bilateral blue scleral pigmentation and blue discoloration to various other dermal areas of his body. The blue pigmentation was also visible in the posterior segment within a scleral crescent around his right optic nerve. This pigmentation was determined to be caused by long-term use of oral minocycline. Conclusions: Long-term minocycline use may induce scleral, dermal, and organ hyperpigmentation, typically blue or black in coloration. The pigmentation may reverse with discontinuation of the medication, but can also be permanent. The exact mechanism of pigment deposition remains uncertain, but several theories have been proposed. While the cosmetic appearance may be dramatic, this side effect is not known to cause any systemic or ocular morbidity.